Characteristics of referrals to national assessment for eligibility into the Specialist Dementia Care Program (SDCP) in Australia. (31st December 2021) - Atee, Mustafa; Morris, Thomas; Macfarlane, Stephen; Cunningham, Colm
Abstract: Background: Dementia is a progressive neurodegenerative disease that is characterized by the presence of behaviors and psychological symptoms (BPSD), such as agitation and hallucinations. BPSD frequently have considerable negative social and clinical outcomes, such as inappropriate drug therapy, caregiver distress, institutionalization, and reduced quality of life. Thus, dementia requires significant care and support, particularly in the advanced stages. A new initiative funded by the Australian Government; the Specialist Dementia Care Programs (SDCPs) provide a person‐centered, multidisciplinary care within special accommodation units for people with severe dementia (up to 12 months) who cannot be cared for by mainstream aged care services. Eligibility assessments for SDCP's placements are conducted by Dementia Support Australia (DSA) through its national Needs Based Assessment (NBA) program (Figure 1). This study describes the referral characteristics of the NBA program. Methods: NBA referrals were deemed eligible for admission to SDCPs if they had: (1) behaviors primarily linked to dementia; (2) severe or very severe BPSD (e.g., aggression, severe agitation); and (3) proved intractable to adequate trials of treatment. Eligibility assessments were completed by a dedicated team of NBA consultants and psychogeriatricians. Demographic data of referrals were described for the period November 2019‐June 2021. Results: Of the 471 referrals (age: 76.0 ± 8.3 y; 69.1% males) received during the specified period, 273 (58.0%) had an NBA assessment. Of these, two‐thirds (n = 178, 65.2%) were found eligible for SDCP placement. Eligible referrals (age: 74.6 ± 7.6 y; 72.3% males) had Alzheimer's disease (n = 93, 52.2%), mixed dementia (n = 27, 15.2%), frontotemporal dementia (n = 17, 9.6%), vascular dementia (n = 14, 7.9%), and dementia with Lewy bodies (n = 8, 4.5%). Most eligible cases were referred from residential aged care homes (RACH; n = 70, 39.8%), hospitals (n = 55, 31.3%) and mental health services (n = 27, 15.3%) because of physical aggression (64.0%). Conclusions: Typical characteristics of eligible NBA referrals to an SDSP placement (i.e., people with severe‐to‐very severe BPSD that require extensive support) included being male, aged on average 75 years old, resided in RACH, physically aggressive towards others, and had Alzheimer's disease.